The emerging role of fumarate as an oncometabolite - Yang, Ming; Soga, Tomoyoshi; Pollard, Patrick J.; Adam, Julie (Frontiers in Oncology, 2012)
The drive to understand how altered cellular metabolism and cancer are linked has caused a paradigm shift in the focus of cancer research. The discovery of a mutated metabolic enzyme, isocitrate dehydrogenase 1, that leads to accumulation of the oncometabolite 2-hydroxyglutarate, provided significant direct evidence that dysfunctional metabolism plays an important role in oncogenesis. Striking parallels exist with the Krebs cycle enzyme fumarate hydratase (FH), a tumor suppressor, whose mutation is associated with the development of leiomyomata, renal cysts, and tumors. Loss of FH enzymatic activity results in accumulation of intracellular fumarate which has been proposed to act as a competitive inhibitor of 2-oxoglutarate-dependent oxygenases including the hypoxia-inducible factor (HIF) hydroxylases, thus activating oncogenic HIF pathways. Interestingly, our studies have questioned the role of HIF and have highlighted other candidate mechanisms, in particular the non-enzymatic modification of cysteine residues (succination) that could lead to disruption or loss of protein functions, dysfunctional cell metabolism and cell signaling. Here, we discuss the evidence for proposing fumarate as an onco-metabolite.